The Interaction between Saccharomyces cerevisiae and Non-Saccharomyces Yeast during Alcoholic Fermentation Is Species and Strain Specific - Wang, Chunxiao; Mas, Albert; Esteve-Zarzoso, Braulio (Frontiers in Microbiology, 2016)
The present study analyzes the lack of culturability of different non-Saccharomyces strains due to interaction with Saccharomyces cerevisiae during alcoholic fermentation. Interaction was followed in mixed fermentations with 1:1 inoculation of S. cerevisiae and ten non-Saccharomyces strains. Starmerella bacillaris, and Torulaspora delbrueckii indicated longer coexistence in mixed fermentations compared with Hanseniaspora uvarum and Metschnikowia pulcherrima. Strain differences in culturability and nutrient consumption (glucose, alanine, ammonium, arginine, or glutamine) were found within each species in mixed fermentation with S. cerevisiae. The interaction was further analyzed using cell-free supernatant from S. cerevisiae and synthetic media mimicking both single fermentations with S. cerevisiae and using mixed fermentations with the corresponding non-Saccharomyces species. Cell-free S. cerevisiae supernatants induced faster culturability loss than synthetic media corresponding to the same fermentation stage. This demonstrated that some metabolites produced by S. cerevisiae played the main role in the decreased culturability of the other non-Saccharomyces yeasts. However, changes in the concentrations of main metabolites had also an effect. Culturability differences were observed among species and strains in culture assays and thus showed distinct tolerance to S. cerevisiae metabolites and fermentation environment. Viability kit and recovery analyses on non-culturable cells verified the existence of viable but not-culturable status. These findings are discussed in the context of interaction between non-Saccharomyces and S. cerevisiae.